Tratamiento quirúrgico del origen anómalo de la arteria pulmonar derecha desde la aorta ascendente: reporte de dos casos - Ocampo Quito, Silvia Lisseth (2025)
The anomalous origin of the right pulmonary artery is a rare congenital cardiac malformation that leads to early development of pulmonary vascular disease, heart failure, and death. Therefore, surgical correction should be performed as soon as the diagnosis is established. A high index of clinical suspicion and the use of non-invasive imaging studies play a crucial role in early diagnosis and timely intervention, thereby reducing the high mortality rates associated with this congenital heart disease. We present two cases of this rare entity, both with clinical manifestations of heart failure from the neonatal period. In both cases, surgical correction was performed through direct anastomosis of the right pulmonary artery to the main pulmonary artery. Both patients showed a favorable postoperative course, with no clinical or echocardiographic evidence of anastomotic stenosis or pulmonary hypertension.